Constraints in writing an essay: agriculture students’ voices - Prasetianto, Mushoffan; Maharddhika, Rizkiana (Journal of Education and Learning (EduLearn), 2025)
Responding to the pivotal role of English nowadays, higher education institutions require every student to take an English course. In higher education, teaching English focuses more on the specific discipline of the students. It helps students to have good English capabilities within their field of study. Writing skill is demanded because the students are required to publish an article as a graduation requirement. In order to find suitable teaching strategies for writing, it is necessary to know the writing difficulty the students encounter. Therefore, the present study aimed to investigate the agriculture students’ difficulty in writing essays. A descriptive qualitative method was employed in this study. The data was obtained from the interviews and students' essays. The result of the study showed that generating ideas, vocabulary, and grammar are the constraints the students faced. This study concludes that the students need a guidance on those constraints.